The transferability of the dual system of vocational education and training - the Korean example : (including 'dos' and 'don'ts' of international TVET cooperation) - Schaack, Klaus [Verfasser] (My University, 1999)
"This report examines the transferability of technical and vocational education and training (TVET) from industrialised to developing countries on the basis of developmental rather than foreign policy. It is suggested that for the transfer of training systems to be successful and sustainable, strategies need to be based on informed analyses of specific country conditions rather than a generalised principle of 'one size fits all'. The aim is to help developing countries build their own training systems appropriate to their own cultural and developmental conditions, while at the same time, enlisting foreign aid and expertise. In an attempt to understand the transfer problems of TVET systems, the author employs Deissinger's theory for the comparison of international education training systems to analyse the possibilities and constraints of establishing a dual system of vocational education and training based on the German model in Korea. The report argues that the traditional one-dimensional definition of the dual training system does not acknowledge that training systems are embedded in a country's historical, cultural, policitical, social and economic relationships. The author goes on to outline the characteristics of a national dual training system using Deissinger's multi-dimensional definition. The application of these criteria are then demonstrated in the Korean context and the results summarised. The report concludes with four examples of training transplantation from industrialised to developing countries to illustrate the implications of introducing a system into a countries with different traditions, cultures and patterns of change and industrialisation." (Authors' abstract, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; S 1.3.1 Ausbildung im Dualen System; S 2.3 Berufsbildungspolitik; I 1.1 Systemberatung; I 2.3.4 Asien; I 2.1 Deutschland; Berufsbildung; Internationale Zusammenarbeit; Duales System; Transfer; Bildungsexpansion; Entwicklungshilfe; Südkorea; Bundesrepublik Deutschland